Desktop versus VR for collaborative sensemaking - Yang, Ying; Dwyer, Tim; Swiecki, Zachari; Lee, Benjamin; Wybrow, Michael; Cordeil, Maxime; Wulandari, Teresa; Thomas, Bruce H.; Billinghurst, Mark (Frontiers in Virtual Reality, 2025)
Immersive environments enable people to share a workspace in a more spatial and embodied manner than traditional desktop collaboration platforms. However, it remains unclear whether such differences support collaborators in sharing information to build mutual understanding during sensemaking. To investigate this, we conducted a user study with groups of four participants—each given exclusive starting information—using mind maps as a medium for information sharing and collaborative sensemaking. Participants used both the VR and desktop systems we developed to complete sensemaking tasks. Our results reveal that the primary focuses of mind-mapping activities differed between VR and desktop: participants in VR engaged more in problem solving, whereas on desktop they concentrated more on mind map organisation. We synthesise our results from post hoc analysis, observations and subjective feedback, and attribute the discrepancies to the fundamental distinctions between the affordances of traditional desktop tools and embodied presence and interactions in VR. We therefore suggest additional features that facilitate mind map authoring and organisation such as automatic mechanisms be considered essential in future immersive mind-mapping systems.